Optimization and anti-optimization solution of combined parameterized and improved interval analyses for structures with uncertainties. (March 2015) - Santoro, R.; Muscolino, G.; Elishakoff, I.
Highlights: Linear discretized structures with uncertain-but-bounded properties are analyzed. Parameterized (PIA) and Improved (IIA-EUI) Interval Analyses are compared. A new method combining PIA and IIA-EUI is presented. The new method by optimization and anti-optimization solution reduces the dependency. Numerical tests show efficiency of the new method to treat structural uncertainties. Abstract: A novel method to deal with structures with uncertain-but-bounded parameters is presented. In order to reduce or eliminate the overestimations due to the so-called dependency phenomenon arising in the classical interval analysis, the authors have recently introduced the parameterized interval analysis and the improved interval analysis via Extra Unitary Interval . The key idea is to develop a new method which, combining the previously two proposed procedures, overcomes their limits and by optimization and anti-optimization problem solutions allows to efficiently solve the set of governing algebraic interval equations in statics.